Design and Development of Motion Graphics to Educate on Dangerous Substances in Lipsticks - จันทร์กระจ่าง, สุรสิทธิ์; สุดปรึก, สิทธิวรรณ; ประวัติรุ่งเรือง, ธีรภัทร; ฐานขันแก้ว, ยุพาวดี; ดีเจริญชิตพงศ์, จิรวิญญ์ (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
The objectives of this research were: 1) to design and develop motion graphic media to educate the public on dangerous substances in lipsticks; 2) to evaluate the quality of the developed media by experts; and 3) to study the satisfaction of the target audience towards the motion graphic media. The sample consisted of 43 adolescents and general individuals interested in cosmetics, selected through purposive sampling. The research instruments included the prototype motion graphic media, quality evaluation forms, and a satisfaction questionnaire. Data were analyzed using mean and standard deviation.            The results indicated the following: 1) The content quality, as evaluated by content experts, yielded a total mean of 4.67 and a standard deviation (S.D.) of 0.18, indicating a very good level of quality. 2) The media quality, as evaluated by media experts, yielded a total mean of 4.72 and a standard deviation (S.D.) of 0.10, also indicating a very good level of quality. 3) The satisfaction of the 43 target participants towards the motion graphic media yielded a mean of 4.55 and a standard deviation (S.D.) of 0.52, reflecting the highest level of satisfaction.